2017
DOI: 10.5897/ajar2016.11995
|View full text |Cite
|
Sign up to set email alerts
|

Controlled water stress in uniformity of maturity and productivity of conilon coffee

Abstract: ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…DACGO is in agreement with that of Haile. ( 2014) with a value of 15.6% and Jorge et al(2017) with a value of 14.70%.While the yield of DRCGO is not in agreement with the study of Ravindranath et al(1972) with a value of 7.9%. The result of DCGOM does not synchronize with the results achieved by…”
Section: Evaluation Of Different Characteristics Of Dcgo Organoleptic...mentioning
confidence: 63%
See 1 more Smart Citation
“…DACGO is in agreement with that of Haile. ( 2014) with a value of 15.6% and Jorge et al(2017) with a value of 14.70%.While the yield of DRCGO is not in agreement with the study of Ravindranath et al(1972) with a value of 7.9%. The result of DCGOM does not synchronize with the results achieved by…”
Section: Evaluation Of Different Characteristics Of Dcgo Organoleptic...mentioning
confidence: 63%
“…Regarding fat content, our results varied between 11.2% -15.01%. It has been reported that CG contained 10-15% (Jenkins et al, 2014), (9.3-16.2%) (Cruz et al, 2012), 20%) (Lago et al, 2001;Martinez-Saez et al, 2017), 15.6% ( Haile, 2014), 14.70% (Jorge et al, 2017) of fats. The variations in content compared to our work are probably related to extraction methods and coffee varieties.…”
Section: Primary Metabolitesmentioning
confidence: 99%
“…No sistema PS, de forma semelhante aos sistemas CB e CI, obteve-se notas intermediárias, quando comparadas aos demais sistemas. É esperado que grãos produzidos em cafezais a pleno sol em regiões quentes, principalmente quando em condições de estresse hídrico, apresentem menor qualidade de bebida devido a alterações na composição bioquímica e maturação incompleta dos frutos (Correa et al, 2017).…”
Section: /6unclassified